The LUCIA beamline at SOLEIL. (15th February 2016) - Vantelon, D.; Trcera, N.; Roy, D.; Moreno, T.; Mailly, D.; Guilet, S.; Metchalkov, E.; Delmotte, F.; Lassalle, B.; Lagarde, Pierre; Flank, A.-M.
Abstract : A review of the improvements made to the LUCIA beamline after it was moved from SLS to SOLEIL is given. Emphasis is given to the new multilayer grating monochromator which extends the energy domain down to around 500 eV. Abstract : Commissioned in May 2004 on the SLS machine, the LUCIA beamline was moved to the synchrotron SOLEIL during the summer of 2008. To take advantage of this new setting several changes to its design were introduced. Here, a review of the various improvements of the mechanics and, mostly, of the optics is given. Described in detail are the results of a new multilayer grating monochromator implemented on the Kohzu vessel already holding the two‐crystal set‐up. It consists of a grating grooved onto a multilayer (replacing the first crystal) associated to a multilayer (as a second crystal). It allows a shift of the low‐energy limit of the beamline to around 500 eV with an energy resolution and a photon flux comparable with those of the previous couples of crystals (KTP and beryl).